Sweat Testing and Recent Advances - KARADAĞ, BÜLENT TANER; GÖKDEMİR, YASEMİN (FRONTIERS MEDIA SA, 2021)
Cystic fibrosis (CF) is the most common fatal genetic disease of the Caucasian population. Sweat testing is the principal diagnostic test for CF, and it is used for the evaluation of infants with positive CF newborn screening (NBS) and in patients with clinical findings suggesting CF. This article describes the classical sweat test method in detail and also provides an overwiew of recent advances.
Keywords: cystic fibrosis; diagnosis; sweat test; Gibson-Cooke; chloride; CYSTIC-FIBROSIS; CLASSIC GIBSON; CLINICAL-EVALUATION; CHLORIDE TITRATION; CONDUCTIVITY TEST; DIAGNOSIS; COOKE; GUIDELINES; SYSTEM; SODIUM